Vacuum and Co-cultivation Agroinfiltration of (Germinated) Seeds Results in Tobacco Rattle Virus (TRV) Mediated Whole-Plant Virus-Induced Gene Silencing (VIGS) in Wheat and Maize - Zhang, Ju; Yu, Deshui; Zhang, Yi; Liu, Kun; Xu, Kedong; Zhang, Fuli; Wang, Jian; Tan, Guangxuan; Nie, Xianhui; Ji, Qiaohua; Zhao, Lu; Li, Chengwei (Frontiers in Plant Science, 2017)
Tobacco rattle virus (TRV)-mediated virus-induced gene silencing (VIGS) has been frequently used in dicots. Here we show that it can also be used in monocots, by presenting a system involving use of a novel infiltration solution (containing acetosyringone, cysteine and Tween 20) that enables whole-plant level VIGS of (germinated) seeds in wheat and maize. Using the established system, phytoene desaturase (PDS) genes were successfully silenced, resulting in typical photo-bleaching symptoms in the leaves of treated wheat and maize. In addition, three wheat homoeoalleles of MLO, a key gene repressing defense responses to powdery mildew in wheat, were simultaneously silenced in susceptible wheat with this system, resulting in it becoming resistant to powdery mildew. The system has the advantages generally associated with TRV-mediated VIGS systems (e.g., high-efficiency, mild virus infection symptoms, and effectiveness in different organs). However, it also has the following further advantages: (germinated) seed-stage agroinfiltration; greater rapidity and convenience; whole-plant level gene silencing; adequately stable transformation; and suitability for studying functions of genes involved in seed germination and early plant development stages.